How England first managed a national infection crisis: Implementation of the Plague Orders of 1578 compared with COVID-19 Lockdown March to May 2020. Issue 1 (2021) - Tobyn, Graeme
Abstract: The current COVID-19 pandemic and lockdown in the UK have parallels with the first ever national management of epidemic infection in England, the Plague Orders of 1578. Combining historical research of the Tudor and Stuart periods with information sources and broadcast news as the epidemic in England unfolds in real time during lockdown, the areas of official guidance, epidemiology, social distancing and quarantine, financing measures, the national health service and fake news are compared. Then as now, limits on freedom of movement and congregation, social distancing and quarantine measures were applied for the sake of preserving life, loss of livelihood ameliorated by government loans and inconvenient opinions suppressed, and these suggest a commonality of organised responses to mass infection across times. Increased danger in certain necessary occupations and flight to second homes by the rich have been observed, health inequities uncovered and restrictions on being with the dying and burying the dead enforced. Wholly unprecedented in comparison with the past, when the wealthiest in a parish were taxed to pay for measures against plague, is the quarantining of the whole society and the financial package for workers on furlough to avoid mass unemployment. In the new normal after lockdown, people should be given more credit for sophisticated understanding than was allowed in past centuries, when fear and punishment coerced the majority to conform, and be allowed access to relevant information which will influence decisions about national and community life going forward after lockdown.